Retraction: Understanding Barriers to PrEP Adherence: A Brief Report on the Combined Effects of Alcohol Misuse, PTSD, and Gut Microbiome Disruption in HIV Prevention - AJPHN, Editor (Asian Journal of Public Health and Nursing, 2025)
Retraction Notice This notice concerns the article: Hasan MR, Davidson R. Understanding Barriers to PrEP Adherence: A Brief Report on the Combined Effects of Alcohol Misuse, PTSD, and Gut Microbiome Disruption in HIV Prevention. Asian Journal of Public Health and Nursing. 2025; 2(2):14–27. https://doi.org/10.62377/ayk4kk55 This article has been retracted at the request of the corresponding author. After publication, the author reported two ethical concerns:(1) inclusion of an institutional affiliation (Norton Hospital) without formal ethics approval or research authorization, and(2) unintentional conceptual overlap with an ongoing institutional research project conducted by senior colleagues.The author acknowledged these issues and requested retraction to maintain transparency and safeguard research integrity. Following editorial review, the Editor-in-Chief approved the retraction in accordance with the journal’s publication ethics policy and the COPE Retraction Guidelines. The original article remains available online for the scholarly record and is clearly marked as RETRACTED. This Retraction Notice is permanently linked to the original publication.